PENGARUH KUALITAS PELAYANAN, SANKSI DAN KESADARAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM PEMBAYARAN PBB DI MOJOSONGO - Fadjar Harimurti, Tri Mustika, Suharno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
This study aims to determine the effect of the quality of tax services, tax penalties and awareness of taxpayers on tax compliance in the payment of property tax. This research is quantitative data collection techniques such as questionnaires and literature study. Analysis of data using multiple linear regression analysis with calculations using SPSS version 21. Partial results of the analysis we concluded that the quality of tax services and a significant positive effect on tax compliance. tax penalties and significant positive effect on tax compliance and taxpayer awareness of positive and significant impact on tax compliance. The results of simultaneous analysis we concluded that the quality of tax services, tax penalties and compulsory awareness positive and significant impact on tax compliance. The results of the analysis of the coefficient of determination obtained value of Adjusted R Square = 0.480 means known that the influence exerted by the independent variable is the quality of tax services, tax penalties and awareness of tax payers by 48% while the remaining 52% is influenced by other variables outside variables studied.Keywords: quality of tax services, tax penalties, awareness of the taxpayer, the taxpayer compliance